Ackerman's surgical pathology - Rosai, Juan (Mosby, 1996)
Cornell University, New York City. Eighth edition of a Brandon/Hill Medical List first-purchase selection. Previous edition 1989. Major two-volume reference for pathologists and residents. Expanded coverage of special techniques, prognostic parameters, and normal anatomy and histology. Halftone illustrations.
Keywords: Pathology, Surgical; chirurgická patologie; patologie